The clinicopathological features of ganglioglioma with CD34 expression and BRAF mutation in patients with epilepsy - Xie, Ming-Guo; Wang, Xiong-Fei; Qiao, Jiao; Zhou, Jian; Guan, Yu-Guang; Li, Tian-Fu; Qi, Xue-Ling; Luan, Guo-Ming (Frontiers in Molecular Neuroscience, 2023)
Objective The aim of the study was to evaluate the clinicopathological features, as well as the surgical prognosis, of epilepsy-associated gangliogliomas (GG) with CD34 expression and BRAFV600E mutation. Methods Clinical data of patients who underwent epilepsy surgery for GG were retrospectively studied. Univariate and multivariate analyses were performed to evaluate the correlations of clinical and pathological factors with molecular markers of CD34 expression and BRAFV600E mutation in GG. Results A total of 208 patients with GG had immunohistochemical detection of CD34 expression (positive/negative: 184/24), and among them, 89 patients had immunohistochemical detection of BRAFV600E mutation (positive/negative: 54/35). By univariate and multivariate analyses, seizure aura (p = 0.025), concordance of ictal electroencephalogram (EEG) findings (p = 0.045) and medial temporal tumor (p = 0.030) were found to be related to CD34 expression, but only hospitalization time (p = 0.042) was different for BRAF-mutated status. In addition, drug-resistant epilepsy (p = 0.040) and concordance of interictal EEG findings (p = 0.009) were found to be associated with tumor progression-free survival (PFS) in univariate analysis, but only concordance of interictal EEG findings was with significance in multivariate analysis. However, CD34 expression or BRAFV600E mutation in GG was not found to be associated with surgical outcomes of seizure control and tumor PFS. Conclusion The CD34 expression or BRAFV600E mutation in GG may partly influence the distribution of clinicopathological features of patients with epilepsy, but they may be not able to predict the surgical prognosis of seizure outcome and tumor recurrence.